Development of Scramble Learning Media to Improve the Character of Love for the Motherland in PKN Pancasila Material - Bella Pertiwi; Pradana Chairy Azhar; Zulham Siregar (research, training and philanthropy institution Natural Aceh, 2023)
Learning media is a tool that can help the teaching and learning process so that the message's meaning becomes clearer and teaching and learning goals can be achieved effectively and efficiently. This research aims to be a learning resource for students to obtain messages and information from teachers so that learning materials can be further improved; this research also focuses on improving the character of love for the homeland through learning media. The type of research used is Research and Development (R&D) using the Borg and Gall method. The steps of use are potential and problems, data collection, product design, design validation, product revision, and limited product trials. Data collection techniques in this study used interviews, questionnaires, and documentation. Based on the analysis of the material expert assessment of 92%, media expert assessment of 86.67%, grade elementary school teacher trial of 90%, individual trial of 91.11%, small group trial of 90.13%, and large group trial of 88%. Thus, scramble learning media can also increase the character of love for the homeland and motivation in the learning process so that students feel happy and excited and do not get bored during the learning process.